2013
DOI: 10.1371/journal.pone.0074938
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of Rapid Evolution in Urban and Rural Transcriptomes of White-Footed Mice (Peromyscus leucopus) in the New York Metropolitan Area

Abstract: Urbanization is a major cause of ecological degradation around the world, and human settlement in large cities is accelerating. New York City (NYC) is one of the oldest and most urbanized cities in North America, but still maintains 20% vegetation cover and substantial populations of some native wildlife. The white-footed mouse, Peromyscus leucopus , is a common resident of NYC’s forest fragments and an emerging model system for examining the evolutionary consequences of urbanization. In this study, we deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 128 publications
(175 reference statements)
2
63
1
Order By: Relevance
“…Our previous study investigated non-synonymous polymorphisms in pooled transcriptome samples and we reported evidence for positive selection in genes dealing with metabolism, immunity, and methylation in NYC white-footed mice (Harris et al 2013). This current study supports the phenotypic traits likely under selection in urban environments, identifying outlier genes that play major roles in metabolism, and to a lesser extent, immunity, but few outlier genes were identified in both the current and previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study investigated non-synonymous polymorphisms in pooled transcriptome samples and we reported evidence for positive selection in genes dealing with metabolism, immunity, and methylation in NYC white-footed mice (Harris et al 2013). This current study supports the phenotypic traits likely under selection in urban environments, identifying outlier genes that play major roles in metabolism, and to a lesser extent, immunity, but few outlier genes were identified in both the current and previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, we randomly chose eight adult white-footed mice (equal numbers of males and females) from each of six sampling locations (N = 48 total) representative of urban and rural habitats and with minimal within-site genetic structure (Fig. 1) (Harris et al 2013, 2015). Three sampling sites were within NYC parks: Central Park in Manhattan (CP), New York Botanical Gardens in the Bronx (NYBG), and Flushing Meadows—Willow Lake in Queens (FM).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also evidence for repeated selection on the SERT gene, which regulates anxiety behavior (e.g., harm avoidance), in European blackbirds across a suite of cities (including Madrid, Berlin, and Prague; Mueller et al 2013). New York City mice also show genetic divergences at loci important for traits like immune response, metabolism, and spermatogenesis (Harris et al 2013). While the latter three studies have shown a genetic basis for a trait change in urban settings, none have determined whether these traits are indeed adaptive (i.e., if there is a reproductive or fitness benefit).…”
Section: Evolution Because Of Urbanizationmentioning
confidence: 99%
“…White-footed mice are abundant in small, fragmented urban forests [14][15][16] and exchange migrants only through vegetated corridors between isolated NYC parks [17]. Substantial genetic structure at microsatellite loci exists between NYC parks [8], and there is evidence of divergence and selection in genes underlying functional traits in urban populations [18].…”
Section: Introductionmentioning
confidence: 99%